2019
DOI: 10.3390/ijerph16060924
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ Difficulties and Expectations for Intervention of Bullying among Young Children in South Korea

Abstract: This study investigated the difficulties of mothers in coping with the bullying of their children and their expectations concerning bullying intervention for young children in South Korea. Twenty mothers with young children were interviewed. Interviews were transcribed in Korean. Nvivo 12 software was used to analyze the data. Four themes emerged: “mothers’ coping strategies”, “problems of interventions”, “expectations of interventions”, and “developmentally appropriate interventions for young children”. Each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…This method may protect the victim only temporarily; the child may have difficulty when facing similar or more severe bullying in the future. This finding was consistent with those of Psalti [61], who found that teachers directed the victim to ignore the bully; of Dereli [42], who found that kindergarten teachers lacked knowledge of alternative functional methods and how to use them to reduce bullying; and of Lee et al [62], who showed that mothers of bullying victims directed their bullied children to avoid the bullying.…”
Section: Resultssupporting
confidence: 86%
“…This method may protect the victim only temporarily; the child may have difficulty when facing similar or more severe bullying in the future. This finding was consistent with those of Psalti [61], who found that teachers directed the victim to ignore the bully; of Dereli [42], who found that kindergarten teachers lacked knowledge of alternative functional methods and how to use them to reduce bullying; and of Lee et al [62], who showed that mothers of bullying victims directed their bullied children to avoid the bullying.…”
Section: Resultssupporting
confidence: 86%
“…Teachers need to recognize the different bullying roles and their various characteristics in terms of peer relationships and power statuses. Kindergarten teachers are likely unaware of bullying in kindergarten [76]. This study highlights the importance of teachers' roles because they are in the best positions to observe children's peer hierarchies.…”
Section: Discussionmentioning
confidence: 83%
“…Alsaker, known as the Bernese Program against Victimization in Kindergarten and Elementary School, which focuses on educating teachers about handling bullying among young children. 32 Strategies such as role playing, victims facing bullying and group support for teenagers as well as the informa tion provided to guide parents can promote prevention and awareness about the adverse effects of being a victim of bullying. These strategies provide victims with skills to defend themselves, which results in a reduction of up to 67% in victimization and 50% in the number of ag gressors.…”
Section: Strategies To Control Bullyingmentioning
confidence: 99%